GREETINGS WORDS OF THE MELAYU COMMUNITY IN MUARA MUSU VILLAGE RAMBAH HILIR SUBDISTRICT ROKAN HULU DISTRICT - Minallah, Fadlan; Arianti, Rita (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
This research discusses the greeting words of the Melayu community of Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency. This research occurs because most children today do not know what greetings to say to others. The research method used is descriptive qualitative method. The purpose of this research is to describe the form of greeting words of the Melayu community of Muara Musu Village. The data of this research is the speech of the community in reprimanding or greeting others in the daily life of the Malay community of Muara Musu Village. The data was found from the community directly when the community said hello and from informants. The results of this study found 53 data of greeting words. Pronouns, proper names, kinship terms, titles and ranks, pe + v forms, N forms, deixis words or clues, nominals, and zero or zero features. The most common greeting words found are kinship greetings and the least are deixis or clue words. The use of greeting words is to show respect to the interlocutor when greeting or speaking. The conclusion of this research is that the use of greeting words is important in our lives because it shows politeness in speaking.